Inhibitory Effect on Cerebral Inflammatory Response following Traumatic Brain Injury in Rats: A Potential Neuroprotective Mechanism of N-Acetylcysteine - Gang Chen; Jixin Shi; Zhigang Hu; Chunhua Hang (Mediators of Inflammation)
Although N-acetylcysteine (NAC) has been shown to be neuroprotective for traumatic brain injury (TBI), the mechanisms for this beneficial effect are still poorly understood. Cerebral inflammation plays an important role in the pathogenesis of secondary brain injury after TBI. However, it has not been investigated whether NAC modulates TBI-induced cerebral inflammatory response. In this work, we investigated the effect of NAC administration on cortical expressions of nuclear factor kappa B (NF-κB) and inflammatory proteins such as interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and intercellular adhesion molecule-1 (ICAM-1) after TBI. As a result, we found that NF-κB, proinflammatory cytokines, and ICAM-1 were increased in all injured animals. In animals given NAC post-TBI, NF-κB, IL-1β, TNF-α, and ICAM-1 were decreased in comparison to vehicle-treated animals. Measures of IL-6 showed no change after NAC treatment. NAC administration reduced brain edema, BBB permeability, and apoptotic index in the injured brain. The results suggest that post-TBI NAC administration may attenuate inflammatory response in the injured rat brain, and this may be one mechanism by which NAC ameliorates secondary brain damage following TBI.